Antioxidant and Anti-inflammatory Activities of Freshwater Macroalga, Cladophora glomerata Kützing - D. Amornlerdpison (2018)
Clodophora glomerata Kützing is an edible filamentous alga. Macroalga has traditionally been consumed as part of an indigenous diet in northern Thailand. The belief of the local people is that the alga could serve to protect against various diseases. Therefore, the aqueous extract of C. glomerata (Aq. C) was examined for antioxidant and anti-inflammatory activities. The Aq. C showed antioxidant activity when tested in the 1-diphenyl-2- picrylhydrazyl (DPPH), superoxide and lipid peroxidation assays at 71, 73, and 66%, respectively. Furthermore, the Aq. C exhibited anti-inflammatory activity, as was shown by evidence obtained from the ethyl phenyl propiolate (EPP)-induced ear edema and carrageenin-induced paw edema experiments in rats. The Aq. C possessed inhibition of the ear and paw thickness at the levels of 58 and 52%, respectively. The mechanism of antiinflammatory activity of Aq. C might be due to its inhibitory effect on the release of some inflammatory mediators. The Aq. C contained phenolic compounds, which the substances associated with antioxidant and anti-inflammatory activities. According to the acute toxicity tests in rats, no deaths or other signs of toxicity were observed. Therefore,the findings could support the premise that C.glomerata is safe for general consumption. From these results, the evidence substantiates the potential of C. glomerata as a food substance oras a nutraceutical product.